[BP.02.02] RATE OF MORNING BLOOD PRESSURE SURGE IS A BETTER PREDICTOR THAN AMPLITUDE FOR 20-YEAR ALL-CAUSE AND CARDIOVASCULAR MORTALITIES: RESULTS OF A COMMUNITY-BASED STUDY. (September 2017) - Cheng, H.; Sung, S.; Wu, C.; Lee, J.; Kario, K.; Chiang, C.; Hsu, P.; Chuang, S.; Wang, W.; Lakatta, E.; Yin, F.; Chou, P.; et al.
Abstract : Objective: Morning blood pressure (BP) surge (MS) is recognized as an important predictor of cardiovascular outcomes. We compared the prognostic values of MS amplitude and rate of BP rise for predicting long-term mortality in a population-based cohort. Figure. No caption available. Design and method: We enrolled 2, 025 participants (984 females, 1, 041 males, aged 30–79 years) with complete demographic and 24-h ambulatory blood pressure monitoring data. During a median 19.7-year follow-up, 607 deaths (119 by cardiovascular causes) were confirmed from the National Death Registry. The amplitude of sleep-trough MS (STMS) was derived from the difference between the morning systolic blood pressure (SBP) and the lowest nighttime SBP. In addition, the rate of MS was derived as the slope of linear regression of sequential SBP measures on time intervals within the STMS period. Results: Thresholds for high MS amplitude and rate were determined by the 95th percentiles (43.7 mmHg and 11.3 mmHg/h, respectively). Multivariable Cox models adjusting for age, sex, body mass index, smoking, alcohol consumption, low-density lipoprotein cholesterol, 24-h SBP, night:day SBP ratio, and anti-hypertensive treatment revealed that a high STMS rate (HR 1.601; 95% CI 1.145–2.237) but not STMS amplitude (1.281 95% CI 0.944–1.737) as significantly associated with greater risk of mortality. Similarly, STMS rate (HR 2.287, 95% CI 1.177–4.444) but not STMS amplitude was significantly associated with the risk of cardiovascular mortality (HR 0.954, 95% CI 0.466–1.951). Conclusions: The STMS rate may be a more sensitive and reliable predictor of mortality than the STMS amplitude. Appropriate management for a rapid STMS should be further investigated.